ANALISIS DIPLOMASI EKONOMI INDONESIA TERHADAP JERMAN: STUDI KASUS EKSPOR KOPI INDONESIA PERIODE 2013-2019 - Fauzan Anggoro Susanto (2022)
Coffee is an agricultural commodity ranked 3rd as a contributor to the country's foreign exchange after palm oil and natural rubber. Indonesia is one of the largest coffee-producing and exporting countries in the world, which competes with Brazil and Vietnam. One of Indonesia's coffee export destinations is Germany, which is the country with the highest level of coffee consumption in the European Union. This makes Germany a very potential country for exporting Indonesian coffee commodities. Seeing this, Indonesia took the initiative to carry out economic diplomacy against Germany in order to increase Indonesian coffee exports to Germany starting in 2013. However, BPS shows the opposite where Indonesia's coffee exports in a period of 6 years starting from 2013-2019 fluctuated and reached their lowest point in 2018 and 2019. Thus, there is a need for a more in-depth analysis of Indonesia's economic diplomacy activities towards Germany which were carried out in the 2013-2019 period. This study aims to explain and analyze Indonesia's economic diplomacy towards Germany to increase Indonesia's coffee exports in the 2013-2019 period. This study uses the theory of economic diplomacy and the concept of international trade with the addition of the concept of export and market access. These theories and concepts are used to assist the writer in analyzing the research questions. The research method used is qualitative, with a case study approach. This type of research is descriptive explanatory because the author does not only want to explain in a narrative manner related to economic diplomacy that has been carried out, but also determines the causes of the phenomena that are the object of research. The results of this study found that forms of commercial diplomacy were more often used by Indonesian delegates than trade diplomacy, such as participating in COTECA, Coffee Workshops, World of Coffee, opening booths in several expo events, and visiting Bandung local government to Braunschweig, Germany. However, these activities only resulted in an increase in German public interest in Indonesian coffee, which did provide a positive trend but only succeeded in the short term. Therefore, it is necessary to carry out economic diplomacy activities in the form of trade diplomacy in order to encourage the success of Indonesia's economic diplomacy in the long term to increase Indonesian coffee exports in the German coffee market.